Simultaneous quantification of dopamine, serotonin, their metabolites and amino acids by LC-MS/MS in mouse brain following repetitive transcranial magnetic stimulation. (December 2019) - Poh, Eugenia Z.; Hahne, Dorothee; Moretti, Jessica; Harvey, Alan R.; Clarke, Michael W.; Rodger, Jennifer
Abstract: Repetitive Transcranial Magnetic Stimulation (rTMS) is a form of non-invasive brain stimulation that has shown therapeutic potential for various nervous system disorders. In addition to its modulatory effects on neuronal excitability, rTMS is capable of altering neurotransmitter (e.g., glutamate, GABA, dopamine and serotonin) concentrations in cortical and subcortical brain regions. Here we used a modified liquid chromatography coupled tandem mass spectrometry (LC-MS/MS) to quantify changes in 27 free amino acids and the monoamines: dopamine (DA), serotonin (5HT) and their metabolites (DOPAC, HVA; 5HIAA) in the mouse brain. Awake C57BL/6 J mice (either sex, 8–12 weeks old) received 10 Hz rTMS using two devices that can deliver low (LI-; 12 mT; custom built) or high (Fo8-; 1.2 T; MagVenture) intensity rTMS. Sham (unstimulated) mice were used as controls. Samples were collected immediately following a single session of rTMS or sham and processed for LC-MS/MS. The modified LC-MS/MS method used to detect DA, 5-HT and their metabolites showed good accuracy and precision with regression coefficients greater than 0.999, and an intra- and inter-day reproducibility with values < 13%. Fo8-rTMS induced a significant reduction in cortical 5-HT turnover rates, hippocampal DOPAC and an increase in striatal DOPAC concentrations. Fo8-rTMS also reduced concentrations of hippocampal α-aminoadipic acid, and striatal serine, threonine, sarcosine, aspartate and glutamate. There were no changes in the level of any compounds following LI-rTMS as compared to sham. The rapid change in monoamine turnover and amino acid concentrations following Fo8-rTMS but not LI-rTMS suggests that different stimulation parameters recruit different cellular mechanisms related to rTMS-induced plasticity. The described method can be used for the characterisation of trace levels of neurotransmitters and amino acids in brain tissue homogenates, providing a useful and precise tool to investigate localised neurotransmitter changes in animal models of health and disease. Highlights: Repetitive transcranial magnetic stimulation (rTMS) alters brain neurochemistry. We developed a method to quantify neurochemicals in brain homogenates after rTMS. rTMS altered cortical and subcortical levels of neurotransmitters and metabolites. Different rTMS parameters had selective effects on neurochemicals. Our method is a precise and sensitive tool to measure neurochemical changes.